PEMBELAJARAN AKHLAK MELALUI KITAB TA’LIMUL MUTA’ALLIM DI PONDOK PESANTREN DAARUL HUDA SUKOHARJO - Santana, Muhammad Frandika Jian; Muh Fajar Shodiq (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This study examines moral learning through the Ta'limul Muta'allim Book at Daarul Huda Islamic Boarding School in Sukoharjo, focusing on methods, strategies, and evaluations in shaping students' morals. Classes occur thrice weekly in the evening, with 40 enthusiastic students participating in a spacious, comfortable hall. Various teaching methods, including bandongan, lectures, and question-answer sessions, create an engaging learning environment. Learning extends beyond the classroom, with teachers providing real-life examples of good morals. Evaluation involves weekly written tests, daily Arabic Pegon Java reading tests, and observation of students' daily behavior. The boarding school setting allows for continuous monitoring of moral development. The ultimate goal is to produce alumni with noble character, following Prophet Muhammad's example, who can serve as benchmarks for Islamic education in society. This approach integrates theory and practice in character formation, preparing students for their future roles. By combining classroom instruction with practical application and continuous evaluation, the school aims to create a holistic learning experience that nurtures both intellectual understanding and moral development in its students.